Social interactions and schooling decisions - Rafael Lalive; Maria Alejandra Cattaneo (Institute for the Study of Labor (IZA), 2006)
The aim of this paper is to study whether schooling choices are affected by social interactions. Such social interactions may be important because children enjoy spending time with other children or parents learn from other parents about the ability of their children. Identification is based on a randomized intervention that grants a cash subsidy encouraging school attendance among a sub-group of eligible children within small rural villages in Mexico. Results indicate that (i) the eligible children tend to attend school more frequently, (ii) but also the ineligible children acquire more schooling when the subsidy is introduced in their local village, (iii) social interactions are economically important, and (iv) they may arise due to changes in parents' perception of their children's ability.
Keywords: C93; I21; I28; 330; peer effects; schooling; field experiment; PROGRESA; Schulauswahl; Soziale Beziehungen; Schätzung; Mexiko